Responses of Plasma Catecholamine, Serotonin, and the Platelet Serotonin Transporter to Cigarette Smoking - Curtis Lee Lowery; Donna Woulfe; Fusun Kilic (Frontiers in Neuroscience, 2019)
Cigarette smoking is one of the major causes of coronary heart disease with a thirty percent mortality rate in the United States. Cigarette smoking acting on the central nervous system (CNS) to stimulate the sympathetic nervous system (SNS) through, which facilitates the secretion of serotonin (5-HT) and catecholamines to supraphysiological levels in blood. The enhanced levels of 5-HT and catecholamines in smokers’ blood are associated with increases in G protein-coupled receptor signaling and serotonylation of small GTPases, which in turn lead to remodeling of cytoskeletal elements to enhance granule secretion and promote unique expression of sialylated N-glycan structures on smokers’ platelets. These mechanisms enhance aggregation and adhesion of smokers’ platelets relative to those of non-smokers. This review focuses on the known mechanisms by which 5-HT and SERT, in coordinated signaling with catecholamines, impacts cigarette smokers’ platelet biology.